Antigen induced production of υ-interferon ex vivo, in the peripheral blood of patients with active pulmonary tuberculosis - Z. M. Zagdyn; A. A. Lutskiy; A. A. Zhirkov; O. A. Makarenko; D. Ferrara; R. Axelsson-Robertson; I. Magalhaes; N. A. Skrynnik; V. N. Shabalin; H. N. Dzhumaeva; M. Maeurer; S. V. Sidorenko; et al. (Журнал инфектологии, 2014)
Tuberculosis (TB) is one of the most significant problems in the Russian Health Care. Russia remains on the list of the 22 countries with a high TB incidence and on the third place in the world with a high prevalence of Drug Resistant TB [1]. It is urgently needed to develop new TB diagnostic methods as well as effective measures of the specific TB prevention, including a development of the novel vaccines, so we have to know better about the most immunogenic antigens of Mycobacterium Tuberculosis. We studied the Interferon-Q production in the whole blood after stimulating immune response with different proteins of Mycobacterium Tuberculosis in patients with active TB. The study results permitted us to evaluate the immunogenicity of the previously known proteins (Ag85a и ESAT-6) in comparison to the recently identified ones (Rv2957, Rv2958c и Rv0447), analyzing simultaneously their relation to tuberculin, as well as to antigens of the different viruses (Human Immunodeficiency Virus, Cytomegalovirus, Epstein-Barr Virus, Influenza Virus). Protein Rv2958c, unlike protein ESAT-6, showed the high immunogenicity in comparison to tuberculin. The expressed immunogenicity of protein Rv2958c might be indicated a possible greatest specificity of immune response to this antigen in TB patients. Meanwhile, bacillary tuberculosis was strongly associated with low immune response to this protein. Also we were found statistical differences in immune responses of patients to the different Mycobacterium Tuberculosis antigens depending on the drug sensitivity. In addition it was interesting to know about a significantly low immune response of patients with Drug Resistant TB to protein pp65 CMV.